Law, ethics, and professional issues for nursing : a reflective and portfolio-building approach - Wheeler, Herman (Abingdon, Oxon : Routledge, 2012)
'This comprehensive new textbook covers core ethical and legal content for pre-registration nursing students. It provides readers with a sound understanding of the interrelationships between the NMC's code of conduct, standards and competencies, ethics and relevant sections of the English legal system. The only truly integrated text in the field, it opens with overviews of law and nursing, and ethical theories and nursing. It goes on to explore key areas of contention - such as negligence, confidentiality and consent - from legal and ethical perspectives, mapping the discussion onto the NMC code of conduct. The chapters include objectives, patient-focused case scenarios, key points, activities, questions, areas for reflection, further reading and a summary. Case law and statutes and ethical theories are presented where appropriate. Written by an experienced nurse-lecturer with a law and ethics teaching background, Law, Ethics and Professional Issues for Nursing is essential reading for all pre-registration nursing students, as well as students of other healthcare professions'--Provided by publisher.
Includes bibliographical references (pages 305-312) and index.
Keywords: Nursing and Midwifery Council (Great Britain).; Nursing -- Law and legislation -- United Kingdom; Nursing ethics -- United Kingdom